Analisis Tingkat Kepuasan Masyarakat Terhadap Penerapan Blu-E Sistem (Smart Card) Pada Pelayanan Pengujian Kendaraan Angkutan Barang (Studi Kasus UPT Pengujian Kendaraan Bermotor Dinas Kota Yogyakarta): Analysis Of Community Satisfaction Level Against Application Of Blu-E System (Smart Card) In Goods Transportation Vehicle Testing Services (Case Study Of UPT Testing Motorized Vehicles Yogyakarta City Service) - Herna Puji Astutik (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Yogyakarta City Department of Transportation (Dishub) officially launched the Electronic Test Passing Proof (BLU-E) or more familiarly known as the Smart Card as proof of passing the KIR test. The BLU-E in the form of a 'smart card' is an innovation to replace the previous test evidence which was still in the form of a book. The form of BLUe itself is shaped like a hologram sticker, with a QR Code, which will be affixed to the windshield of the freight vehicle. By replacing the proof of vehicle testing using the old method in the form of a KIR book with a smart card, the community will certainly experience changes in habits which of course need to be measured to know the response to the level of community satisfaction. The research method is in the form of descriptive quantitative by utilizing the SERVQUAL Dimension used to assess customer satisfaction consisting of tangible, reliability, responsiveness, assurance, and empathy. Methods of data collection by filling out questionnaires. From the calculation above results, the service user satisfaction index value is 88%. So, based on the rating interval, it can be concluded that the respondent was